Rapid HIV Antigen–Antibody Assays and detection of acute HIV infection in sub-saharan Africa (2019)
Detection of acute HIV infection is a unique problem that fourth-generation HIV assays were expected to alleviate. In this commentary, we draw attention to the limitations and challenges with use of currently available rapid antigen–antibody (Ag/Ab) combination tests for detection of acute HIV infection in sub-Saharan Africa. Laboratory-based HIV-1 Ag/Ab immunoassays are complex, requiring specialized equipment and handling that are currently not affordable in many settings in Africa. The point-of-care Ag/Ab platform on the other hand is easier to deploy and potentially more accessible in resource-limited settings. However, available fourth-generation HIV-1 rapid diagnostic tests have demonstrated poor performance characteristics in field studies where non-B subtypes of HIV-1 dominate. The potential for point-of-care HIV-1 Ag/Ab diagnostics to significantly improve detection of acute HIV infection remains yet to be realized in sub-Saharan Africa. Assay platforms need to be optimized to identify local circulating subtypes, and optimal algorithms need to be determined